Análisis de las secuencias codificantes de los genes relacionados con la respuesta inmunitaria a los parásitos nematodos. - Vásquez Salazar, Kerly Daniela (2021)
This research project is based on a documentary methodology, where the analysis of the coding sequences of the genes related to the immune response to parasites was developed, in this case Nematodes, this information will be essential for biotechnologists in the elaboration of a DNA vaccine in order to create immunity in the different animal species, and reduce the excessive use of dewormers that many of the times have no effect, thus reducing management expenses and increasing the economy of domestic animal producers . For this, the main immunological genes in the Nematode Parasites of the different animal species were collected and selected, such as: canines, felines, bovines, pigs, horses, sheep, goats, South American camelids, birds (hen, goose, turkey and duck). This information was obtained through the National Center for Biotechnology Information (NCBI), said system provided essential information such as functions, structure and location (both cellular and chromosomal) of genes, the clinical effects of mutations, as well as the similarities between sequences and biological structures of each of the nematode parasites, once the necessary information was collected, a database was generated distributed by: animal species, gene, location, chromosome, number of exons, exons related to the response immune system, mRNA sequence, immunity, pathologies where evidence and reference were made, thanks to this database, the results obtained were obtained to obtain the promoter regions of each gene related to the immune response, which are: Canines: exon 3 and 4 of IFN-g, exon 1 and 5 of IL-10; Felines: exon 2 of IFN-g; Porcine: intron 1 of TNF-α; Equine: exon 1 of TNF-α and exon 4 of IFN-g; Sheep: intron 1 and 3 of IFN-g; Goat: intron 1 of IFN-g; Poultry (Chicken and Ducks): exon 4 of IFN-g in chickens and exon 5 of IFN-g in ducks. These promoter regions were considered essential for giving an immune response to the presence of Nematodes parasites in each animal species and contributing to the elimination of parasites, preventing their replication and favoring resistance to the development of the disease. Therefore, these coding sequences are main candidates for the elaboration of DNA vaccines and thus generate immunity in the different animal species against the diseases caused by these parasites.